Rendas, redes e lendas: O vocabulário das rendeiras do município de Raposa, Maranhão - Raquel Pires Costa (2016)
Lexical studies, to gather together the linguistic and non-linguistic, provide data for the reading of a societys culture. In Brazil, there is still much to be researched in this sense, because there are several locations with peculiar linguistic characteristics, especially in lexical scope: there are numerous words and expressions that portray the lexicon of a speech community. One of them is the city of Raposa, state of Maranhao, located approximately 28 km from the state capital, São Luís. Its formation was due to the migration of fishing families who have left their homeland, Acaraú, Ceará, in the 50s due to a extreme dry weather. In this migration, women took with them the beautiful tradition of bilro lace, craft still present among them until today in the fishing community of this Maranhãos city. Basing ourselves on the theoretical-methodological assumptions of Sociolinguistics (Labov and Milroy), Lexicology (Biderman), Lexicography (Barbosa, Esquivel and Haensch) and Linguistic Anthropology (Duranti, Hymes and Velarde), we described and analyzed the vocabulary of the Raposas craftswomen. Following the guidelines of Linguistic Anthropology and Sociolinguistics, we collected and transcribed data derived from the 15 oral interviews made on Raposa. We returned to the past, consulting the 207 words selected in the eighteenth (Bluteau) and nineteenth (Morais) century dictionaries, in one of the first half of the twentieth century (Laudelino Freire) and then we came back to present, consulting them in contemporary dictionaries, in order to make comparisons among these periods. In order to see its origin, we consulted etymological dictionaries. After the research to dictionaries, we did qualitative and quantitative analysis, which demonstrated the existence of a peculiar vocabulary, revealing the close relationship between language and culture, the intersection between the world of the craftwomen and the fishermen and rescuing social and historical aspects of the life of the craftwomen. In the glossary resulting of the research, the words used to designate points, objects and actions related to the culture of the handcraft have great spotlight and reveal its wealth as well as the creativity of the craftwomen in the act of nominate .